On Generalized Moduli of Quasi-Banach Space. (3rd May 2018) - Kwun, Young Chel; Ahmad Qadri, Hussain Minhaj Uddin; Nazeer, Waqas; Haq, Absar Ul; Kang, Shin Min
Abstract : We shall discuss three generalized moduli such as generalized modulus of convexity, modulus of smoothness, and modulus of Zou-Cui of quasi-Banach spaces and give some important properties of these moduli. Furthermore, we establish relationships of these generalized moduli with each other.